Pengaruh Pendidikan, Profesi Dan Bagi Hasil Terhadap Persepsi Masyarakat Pada Perbankan Syariah - Sri Rahmany; Yuni Asnita (JPS (Jurnal Perbankan Syariah), 2020)
This research aims to determine whether education, profession and profit-sharing partially and simultaneously affect public perceptions of sharia banking in Siak Kecil District. The data analysis technique used is the validity test, reliability test, normality test, multiple linear regression test, t-test, f test and the coefficient of determination test. The results of this study found that the level of education did not significantly influence people's perceptions of Islamic banking in Siak Kecil District. Then in terms of the profession, there is a significant influence on people's perceptions of Islamic banking in the Siak Kecil District. In terms of revenue sharing, there is a significant influence on people's perceptions of Islamic banking in Siak Kecil District. Simultaneously education, profession and profit-sharing affect people's perceptions of Islamic banking in Siak Kecil District with a large influence of 55.4%.